Sociological Dynamics of Indonesian Islamic Education: Mastery of Information and Communication Technology (ICT) Literacy by Teachers of SMPN 3 South Tangerang City - Reksiana, Reksiana; Rafikjon Ugli, Abdulbosit R.; Alsamairi, Ali Mohammed A.; Wulansari, Nurbaini F; S Elkoshli, Eiman Massud (JURNAL INDO-ISLAMIKA, 2024)
The study highlights challenges faced by some Islamic Religious Education (PAI) teachers at SMPN 3 Tangerang Selatan in integrating ICT media into learning. Commonly used tools include YouTube, PowerPoint, Google Classroom, and Google. This research analyzes the ICT literacy proficiency of PAI teachers using a qualitative method with a phenomenological approach. Primary data were obtained from two PAI teachers, the vice-principal, and students, while secondary data included curriculum books, school archives, and related documents. Data collection involved non-participant observation and semi-structured interviews, with documents such as curriculum, syllabi, and lesson plans (RPP) analyzed. Following Tammy Moerer-Urdahl and John W. Creswell's phenomenological model, the steps included describing teachers’ experiences (epoche), identifying significant statements, grouping them into themes, and synthesizing themes into comprehensive descriptions. The findings offer insights into ICT literacy levels and reveal the ongoing struggles teachers face in effectively incorporating technology into PAI learning processes.